2012
DOI: 10.1177/0306312712457110
|View full text |Cite
|
Sign up to set email alerts
|

Pig towers and in vitro meat: Disclosing moral worlds by design

Abstract: Technology development is often considered to obfuscate democratic decision-making and is met with ethical suspicion. However, new technologies also can open up issues for societal debate and generate fresh moral engagements. This paper discusses two technological projects: schemes for pig farming in high-rise agro-production parks that came to be known as 'pig towers', and efforts to develop techniques for producing meat without animals by using stem cells, labelled 'in vitro meat'. Even before fully entering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 48 publications
(42 reference statements)
0
26
0
4
Order By: Relevance
“…There is, in fact, a considerable gap between culturing a relatively small quantity of cells in vitro and developing a marketable product. It seems risky to rely on a few tests carried out by the project financiers (such as People for the Ethical Treatment of Animals (PETA), i.e., stakeholders with a vested interest) using 'artificial chicken' products which indicated their good reception by consumers (Driessen and Korthals 2012). Major challenges ahead pertain to further improving the product and its production process in order to make it mimic traditional meat (based on the insights of the present study, notably in terms of sensory characteristics and price), up-scaling the process and making it more resource-and cost-efficient, and dealing with regulatory and intellectual property issues (Post 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is, in fact, a considerable gap between culturing a relatively small quantity of cells in vitro and developing a marketable product. It seems risky to rely on a few tests carried out by the project financiers (such as People for the Ethical Treatment of Animals (PETA), i.e., stakeholders with a vested interest) using 'artificial chicken' products which indicated their good reception by consumers (Driessen and Korthals 2012). Major challenges ahead pertain to further improving the product and its production process in order to make it mimic traditional meat (based on the insights of the present study, notably in terms of sensory characteristics and price), up-scaling the process and making it more resource-and cost-efficient, and dealing with regulatory and intellectual property issues (Post 2014).…”
Section: Discussionmentioning
confidence: 99%
“…An interesting remark is the fact that even positive intended information can fuel consumer resistance because it can increase awareness of previously unknown risks (Verbeke et al 2007). Driessen and Korthals (2012) mentioned the fact that the development of cultured meat had already given rise to heightened media attention in the Netherlands, for example, and this prior to the highly publicized tasting of the first cultured meat burger in August 2013 in London (Hopkins 2015). Goodwin and Shoulders (2013) analysed the media coverage about cultured meat in the United States (U.S.) and the European Union (prior to the August 2013 cultured burger tasting) and concluded that print media were primarily supporting the idea of cultured meat production.…”
Section: Criteria Shaping Consumer Acceptancementioning
confidence: 99%
See 1 more Smart Citation
“…In light of such, it is unsurprising that those with a vested interest in various forms of animal exploitation will not simply accept that their activities are inconsistent with the technical efficiency mode of evaluation associated with the industrial common world. Thus, and at the same time that animal rights activists have sought to promote the efficiency of a vegan diet, shmeat, and so on, the livestock industry, and other interested parties, have proposed such things as 'pig towers', or what amounts to a more efficient method of intensive pig farming (Driessen, 2012).…”
Section: Aligning Common Worlds In An Opportunistic and Cumulative Famentioning
confidence: 99%
“…While names such as 'Labchops' and 'Meat 2.0' have previously been put forward (Driessen and Korthals, 2012), proponents today increasingly settle for 'cultured' meat (Datar, 2016).…”
mentioning
confidence: 99%